PENERAPAN PENDEKATAN KLASIK, HUMAN RELATION, DAN SUMBER DAYA MANUSIA PADA MANAJEMEN SEKOLAH DI MTSN 1 LANGKAT: STUDI KASUS - Muhammad Ikhza Elsya; Muhammad Al- Fatih; Neliwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of the classical, human relations, and human resources approaches in school management at MTsN 1 Langkat and analyze their impact on the effectiveness of school management. The study employed a qualitative case study approach. Data were collected through observation, semi-structured interviews, and documentation studies. Data analysis involved data reduction, data presentation, and descriptive conclusion drawing. The results indicate that the classical approach is implemented through a clear organizational structure, detailed division of tasks, and an orderly administration system. The human relations approach is evident in open communication, harmonious working relationships, and the involvement of teachers and other educational staff in decision-making. The human resources approach is implemented through competency development, performance evaluation, and rewards for school personnel. The integrated implementation of these three approaches positively contributes to the effectiveness of school management, increasing organizational order, work motivation, and the professionalism of school personnel.